Evaluating the Effectiveness of Using Digital Technologies in Music Education - Gagica Rexhepi, Flutura; Kryeziu Breznica, Rreze; Reshat Rexhepi, Burhan (Journal of educational technology development and exchange, 2024)
The relevance of the study of the effectiveness of digital technologies in music education lies in the need to adapt modern music education to the requirements of the digital world. The purpose of this study was to evaluate the effectiveness of digital technologies in music education and to determine their impact on the quality of music education. The methods used in the study were the statistical method, modelling, the method of generalising experience, as well as experimentation and theoretical analysis. The results of the study showed that the use of modern digital technologies in music education could make the learning process more effective and accessible. Students who used digital resources and tools learned music material better, expressed more interest in learning, developed better creative skills, and were involved in teamwork on music projects. The use of digital technology had also helped to optimise time and preserve music resources. In general, this is a major step in improving music education and the development of pupils and students.